The Relationship of Eye and Hands Coordination on Badminton Netting Shots at Tamasya PB Guardians Oku - Yasa, Ibnu; Syafaruddin, Syafaruddin; Usra, Meirizal (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
Net shots in a match play a very important role because they can make it difficult for the opponent to take the shuttlecock properly if they hit the net correctly. In netting, the coordination of the eyes and hands plays a very important role when the opponent's ball comes towards the front, the hand starts the stance to hit the shuttlecock slowly and in a straight or crossed direction, either to the right or left. This study aims to determine the relationship between eye-hand coordination and netting shots. This research is quantitative research with correlational techniques. The research sample consisted of 30 respondents who were assisted by PB Tamasya OKU. Sampling used the total sampling method. Data collection used the tennis ball throwing and catching test as an instrument to test hand-eye coordination and the netting test as an instrument to test netting hitting ability. Data analysis was carried out univariately and bivariately with the Chi Square test at a confidence level of 95% with a significance value of p value ≤ 0.005, then Ha was accepted and p value > 0.005, then Ha was rejected. The results of the statistical test between the independent variable and the dependent variable obtained a significant value (p value) of 0.000, which shows that there is a relationship between eye and hand coordination and netting strokes in PB Tamasya OKU's coaching staff..